Klasifikasi Emosi Tokoh dalam Novel Surga yang Tak Dirindukan Karya Asma Nadia: Kajian Psikologi Sastra - Khasanah, Afita Dwi; M, Hannifia Dalia Azza; Ilawati, Ilawati; Nabilla, Jihan Ainas; Pamungkas, Onok Yayang (CV. Eduartpia Publisher, 2025)
This research aims to describe the classification of emotions in the novel Surga Yang Tak Missed by Asma Nadia. The method used in this research is a qualitative descriptive method with a literary psychology approach. The data source used is the novel Heaven that is Not Missed by Asma Nadia with a thickness of 300 pages and the data used is in the form of quotes or paragraphs that describe the form of emotional classification. Data was collected using reading and note-taking techniques and analyzed by identifying forms of emotional classification, grouping, and inferring or drawing conclusions from the data obtained. The results of the research show that in the novel Heaven that is Not Missed there are seven forms of emotional classification according to David Krech's perspective, namely: the emotional classification of guilt is 2 data, the feeling of buried guilt is 2 data, self-punishment is 2 data, shame is 3 data, sadness with 6 data, hatred with 3 data, and classification of emotions in the form of love with 2 data. From the research above, it can be concluded that the most dominant data is the classification of emotions in the form of sadness